A comprehensive review on 3D printing advancements in polymer composites: technologies, materials, and applications - Jagadeesh, Praveenkumara; Puttegowda, Madhu; Rangappa, Sanjay Mavinkere; Alexey, Karfidov; Gorbatyuk, Sergey; Khan, Anish; Doddamani, Mrityunjay; Siengchin, Suchart (International journal of advanced manufacturing technology, 2022)
3D printing is a constantly expanding technology that represents one of the most exciting and disruptive production possibilities available today. This technology has gained global recognition and garnered considerable attention in recent years. However, technological breakthroughs, particularly in the field of material science, continue to be the focus of research, particularly in terms of future advancements. The 3D printing techniques are employed for the manufacturing of advanced multifunctional polymer composites due to their mass customization, freedom of design, capability to print complex 3D structures, and rapid prototyping. The advantages of 3D printing with multipurpose materials enable solutions in challenging locations such as outer space and extreme weather conditions where human involvement is not possible. Each year, numerous research papers are published on the subject of imbuing composites with various capabilities such as magnetic, sensing, thermal, embedded circuitry, self-healing, and conductive qualities by the use of innovative materials and printing technologies. This review article discusses the various 3D printing techniques used in the manufacture of polymer composites, the various types of reinforced polymer composites (fibers, nanomaterials, and particles reinforcements), the characterization of 3D printed parts, and their applications in a various industries. Additionally, this review discussed the limitations of 3D printing processes, which may assist future researchers in increasing the utility of their works and overcoming the shortcomings of previous works. Additionally, this paper discusses processing difficulties, anisotropic behavior, stimuli-responsive characteristics (shape memory and self-healing materials), CAD constraints, layer-by-layer appearance, and void formation in printed composites. Eventually, the promise of maturing technology is discussed, along with recommendations for research activities that are desperately required to realize the immense potential of operational 3D printing.